STRATEGI REKRUTMEN DAN SELEKSI UNTUK MENUNJANG PERSIAPAN KERJA BAGI PESERTA PELATIHAN UNIT PELAKSANA TEKNIS (UPT) - BALAI LATIHAN KERJA (BLK) KABUPATEN BOGOR - Hasyim, Moch. Sarif; Hartanto, Hartanto; Wardoyo, Bambang; Adil, Athira Setira; Putu Nia Anggraeni, Ni Luh; Abrian Kusuma, Muh. Eko; Masliardi, Adi; Mardiyanto, Doni; Ardianti, Devi Nurvita; Dyfa, Rachma Maulida; Br Sembiring, Santa Feronika; Santosa, Dony Firman (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
Bogor Regency is among the top three regions with the highest unemployment rate in West Java Province after Bogor City and Cimahi City (Open Unemployment Rate / TPT data released by BPS West Java Province as of August 2022). Therefore, efforts are needed to reduce the unemployment rate. The importance of job preparation for trainees requires an appropriate approach in the recruitment and selection process to ensure the suitability of participants with the programs offered. The purpose of implementing this community service is to increase participants' knowledge and skills in making job application letters and ATS CVs, improve skills in taking psychological tests and interview techniques, improve skills in building leaderless group discussions and equip soft skills to support job preparation. The method of implementation is through training which includes lecture, simulation, discussion and practice methods so that participants really understand and are able to apply well. The participants of the community service program consisted of 41 participants from the Bogor Regency Job Training Center (BLK). The results obtained from community service activities are an increase in the participants' understanding and skills in making CVs, application letters, taking psychological tests, conducting interviews, FGDs and soft skills. This is reinforced by the positive response and satisfaction level of the participants as well as the increase in post test scores. Keywords: Recruitment, Training, Skills, Job Selection